Power plays enriched uranium and homeland security - Hubbard, Christopher, 1953- (Homeland security series, 2010)
Offers a comprehensive exploration of the effects on national/state security policy and discourse of the production, storage, transportation, safeguarding, export and use of enriched uranium and by extension, plutonium.